Examining the impact of HIV-related stigma in people living with HIV: a systematic literature review - Nyashanu, Mathew; Mushonga, Florence Tafadzwa Ellah; Dada, Samuel Oluwasogo; Ekpenyong, Mandu Stephen (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
The last 20 years have seen an improvement in access to anti-retroviral (ARVs) drugs for people living with HIV leading to improvement in health outcomes. However, despite achieving this milestone HIV stigma has continued to hamper the health outcomes of people living with HIV. This study aimed to undergo a systematic review exploring the impact of HIV stigma on people living with HIV. A systematic literature review of both quantitative and qualitative studies published between 2017 and 2021 was undertaken using the following databases: CINAHL Plus, Embase, Google Scholar, Medline, and Scopus. Reference lists from relevant studies and websites of relevant sexual health and HIV organisations were also searched. The primary search terms were “HIV and stigma” combined with “impact” or with “discrimination”, “internalised stigma” and “lack of esteem”, or “mental health” or “caused by HIV sigma” in communities, “HIV and discrimination”, “impact of HIV stigma”. Six articles were included for review and analysed using constant comparative analysis. The review identified six broad themes (lack of adherence, internalised HIV stigma, discrimination, lack of self-esteem, public stereotyping, and non-disclosure) factors having a significant influence on people living with HIV. Perceived stigma towards people living with HIV has a negative effect on health outcomes of people living with the condition. The findings of our study highlight that public stereotyping and perceived stigma in the community are the major factors impacting people living with HIV.